Gonadotrophin releasing hormone antagonist in IVF/ICSI - M S Kamath; A M Mangalraj; K M Muthukumar; K George (Wolters Kluwer Medknow Publications, 2008)
Objective : To study the efficacy of gonadotrophin releasing hormone (GnRH) antagonist in In-vitro-fertilization/Intracytoplasmic sperm injection (IVF/ICSI) cycles. Type of Study : Observational study. Setting: Reproductive Medicine Unit, Christian Medical College Hospital, Vellore, Tamil Nadu. Materials and Methods: GnRH antagonists were introduced into our practice in November 2005. Fifty-two women undergoing the antagonist protocol were studied and information gathered regarding patient profile, treatment parameters (total gonadotrophin dosage, duration of treatment, and oocyte yield), and outcomes in terms of embryological parameters (cleavage rates, implantation rates) and clinical pregnancy. These parameters were compared with 121 women undergoing the standard long protocol. The costs between the two groups were also compared. Main Outcome : Clinical pregnancy rate. Results : The clinical pregnancy rate per embryo transfer in the antagonist group was 31.7% which was comparable to the clinical pregnancy rate in women undergoing the standard long protocol (30.63%). The costs between the two groups were comparable. Conclusions : GnRH antagonist protocol was found to be effective and comparable to the standard long protocol regimen. In addition it was simple, convenient, and patient friendly.